Studi Perbandingan Kemampuan Literasi Matematika Siswa Antara Penggunaan Media Geogebra dan Media Manipulatif - Sinta Dian Ulandari; Feri Noperman (Universitas Bengkulu, 2023)
This study aims to determine the ratio of students' mathematical literacy skills between the use of media learning geogebra and learning media manipulative on the material of building nets in class V SDN Bengkulu City. This type of research is quantitative with Quasi Experimental Design method. The design of this research is Pretest-Posttest Comperations Group Design. The population in this study is all students of Bengkulu State Elementary School which accredited B and is an impact school. The sample in this research is the students of VA SDN 18 Kota Bengkulu class as experimental group I and the students of VB SDN 18 Kota Bengkulu as experiment group II. The test is done twice before and after giving treatment to the sample class. The research instrument used is a test with essay form for process components, multiple choice for content component, and assignment for context component. Data of this research are analyzed by using descriptive analysis and inferential analysis that is t-test (independent sample t-test). The result showed that the average value of pretest of experiment class I was 25,300, the average value of pretest of experiment class II was 33,710, the average value of posttest of experiment class I was 65,710, and the mean value of posttest of experiment class II was 54,530. The result of pretest-t test in experiment class I and experiment class II showed significance value of 0.003 <0.025. The result of posttest t-test on experiment class I and experiment class II shows significance value equal to 0,009 <0,0250. Furthermore, the t-test for the gain value obtained by the significance value of 0.000 <0,0250 means there is a difference. It can be concluded that H0 is rejected and Ha accepted, it means there are differences of students' mathematical literacy ability between usage of learning media of geogebra and manipulative learning media on the material of building nets in class V SDN Bengkulu city.